2019
DOI: 10.1208/s12249-019-1408-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid Carrier of Propofol: a Promising Alternative to Marketed Soybean Oil–Based Nanoemulsion

Abstract: Nanostructured lipid carrier (NLC) of propofol was formulated using hot emulsification-probe sonication method for improvising its parenteral delivery by reducing pain on injection and risk of microbial contamination. The formulated NLC was optimized using central composite design and evaluated for particle size, zeta potential, morphology, free propofol concentration, hemocompatibility, stability, pain on injection, in vivo anesthetic activity, pharmacokinetics, and antimicrobial effectiveness in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…It was observed that the particle size of EZ-NLC formulations ranged from 160.95 ± 19.31 to 506.7 ± 11.29 nm. Generally, the incorporation of two emulsifiers (tween 80 and poloxamer 188) with different HLB values played an important role in varying the particle size of different EZ-NLC formulations . Tween 80 was chosen from a range of surfactants owing to its regulatory approval and ability to effectively prepare a variety of NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the particle size of EZ-NLC formulations ranged from 160.95 ± 19.31 to 506.7 ± 11.29 nm. Generally, the incorporation of two emulsifiers (tween 80 and poloxamer 188) with different HLB values played an important role in varying the particle size of different EZ-NLC formulations . Tween 80 was chosen from a range of surfactants owing to its regulatory approval and ability to effectively prepare a variety of NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…[11,90] To tackle these challenges, numerous innovative nano-formulations have been developed to enhance the efficacy and safety of propofol, while avoiding the use of soybean oil and disodium edetate. [11,90,91] For example, Shevalkar et al devised a nanostructured lipid carrier (NLC) of propofol using the hot emulsification-probe sonication method and refined the combinations of solid lipids, oils and surfactants. This optimized NLC formulation not only reduced the content of free propofol in the aqueous phase by 40%, thereby alleviating injection pain compared to Diprivan, but also exhibited other favorable attributes such as non-hemolysis, comparable pharmacokinetics, reduced risk of hyperlipidemia, improved long-term storage stability, and antimicrobial properties.…”
Section: Nanoformulation Of Anesthetics With Good Safetymentioning
confidence: 99%
“…To achieve the necessary concentration for effectiveness, current commercially available etomidate formulations utilize either lipid emulsion (e.g., Etomidate-Lipuro) or propylene glycol (e.g., Amidate) as solubilizing agents. [11] However, these solubilizing agents have been associated with various adverse events, including propylene [83] Copyright 2022, Chu et al, open access. b) Selfassembling APK peptides form antibacterial nanofiber that can be used as a safe nano-formulation for etomidate.…”
Section: Nanoformulation Of Anesthetics With Good Safetymentioning
confidence: 99%
“… Propofol Haemolysis The degree of hemolysis is within an acceptable range. [98] Stearic acid Hot melt homogenization method p.o. Simvastatin Haemolysis Treatment of rats with SV preparations will weaken the hemolysis of RBCs, and SV can reverse hyperlipidemia and cause changes in RBCs membrane fluidity.…”
Section: Hemocompatibility Characteristics or Improvement Strategies Of Various Nanocarriersmentioning
confidence: 99%